Patterns of failure after immunotherapy with checkpoint inhibitors predict durable progression-free survival after local therapy for metastatic melanoma. Issue 1 (24th July 2019) - Klemen, Nicholas D.; Wang, Melinda; Feingold, Paul L.; Cooper, Kirsten; Pavri, Sabrina N.; Han, Dale; Detterbeck, Frank C.; Boffa, Daniel J.; Khan, Sajid A.; Olino, Kelly; Clune, James; Ariyan, Stephan; et al.
Abstract : Background: Checkpoint inhibitors (CPI) have revolutionized the treatment of metastatic melanoma, but most patients treated with CPI eventually develop progressive disease. Local therapy including surgery, ablation or stereotactic body radiotherapy (SBRT) may be useful to manage limited progression, but criteria for patient selection have not been established. Previous work has suggested progression-free survival (PFS) after local therapy is associated with patterns of immunotherapy failure, but this has not been studied in patients treated with CPI. Methods: We analyzed clinical data from patients with metastatic melanoma who were treated with antibodies against CTLA-4, PD-1 or PD-L1, either as single-agent or combination therapy, and identified those who had disease progression in 1 to 3 sites managed with local therapy. Patterns of CPI failure were designated by independent radiological review as growth of established metastases or appearance of new metastases. Local therapy for diagnosis, palliation or CNS metastases was excluded. Results: Four hundred twenty-eight patients with metastatic melanoma received treatment with CPI from 2007 to 2018. Seventy-seven have ongoing complete responses while 69 died within 6 months of starting CPI; of the remaining 282 patients, 52 (18%) were treated with local therapy meeting our inclusion criteria. Local therapy to achieve no evidence of disease (NED) was associated with three-year progression-free survival (PFS) of 31% and five-year disease-specific survival (DSS) of 60%. Stratified by patterns of failure, patients with progression in established tumors had three-year PFS of 70%, while those with new metastases had three-year PFS of 6% ( P  = 0.001). Five-year DSS after local therapy was 93% versus 31%, respectively ( P  = 0.046). Conclusions: Local therapy for oligoprogression after CPI can result in durable PFS in selected patients. We observed that patterns of failure seen during or after CPI treatment are strongly associated with PFS after local therapy, and may represent a useful criterion for patient selection. This experience suggests there may be an increased role for local therapy in patients being treated with immunotherapy.